Intrapartum and perinatal results associated with different degrees of staining of meconium stained amniotic fluid - Rodríguez Fernández, Vanesa; López Ramón y Cajal, Carlos Nicolás; Marín Ortiz, Elena; Couceiro Naveira, Emilio (European journal of obstetrics & gynecology and reproductive biology, 2018)
To determine the intrapartum and perinatal results associated with different degrees of staining of meconium stained amniotic fluid (MSAF). In a retrospective cohort study of all singleton deliveries over a period of one year (2015) in a tertiary hospital, we compared different degrees of MSAF (yellow, green and thick) to clear amniotic fluids, and analysed in each group maternal, intrapartum and neonatal variables as well as umbilical cord blood gas analysis. Of the 3590 deliveries included, 503 (14%) had MSAF. The incidence of MSAF rises with gestational age at delivery, reaching 20.7% in gestations above 41 weeks compared to 4.3% below 37 weeks. As the amniotic fluid staining progresses we found a higher proportion of intrapartum fevers (p < 0.001), pathological fetal heart rate patterns (p < 0.05), operative vaginal deliveries and cesarean sections (p < 0.001), as well as the need for advanced neonatal resuscitation (p < 0.001). There was also a correlation between MSAF and low Apgar scores at five minutes (p < 0.001) and fetal-neonatal mortality (p < 0.001) but there was not a higher proportion of neonatal intensive care admissions (p > 0.05). We have observed a similar distribution of umbilical artery pH ranges in all groups (p > 0.05). MSAF was associated with an increase in the rate of pathological fetal heart rate patterns, intrapartum fevers, operative vaginal and cesarean section deliveries, need for neonatal resuscitation, low Apgar scores and higher fetal-neonatal mortality. Moreover, we found that the risks increase as the staining and consistency of the amniotic fluid evolves so it should alert the obstetrician and paediatrician to the potential adverse outcomes.